Interface‐Rich Three‐Dimensional Au‐Doped PtBi Intermetallics as Highly Effective Anode Catalysts for Application in Alkaline Ethylene Glycol Fuel Cells. (23rd June 2021) - Yang, Xiaotong; Yao, Ke xin; Ye, Jin Yu; Yuan, Qiang; Zhao, Fengling; Li, Yongfei; Zhou, Zhiyou
Abstract: The preparation of metal electrocatalysts with excellent comprehensive properties for application in alcohol fuel cells is an urgent issue. This study reports a novel 3D Au‐doped PtBi intermetallic phase woven by sub‐7 nm building blocks. The high‐efficiency "active auxiliary" Au advances the activity and in situ anti‐CO poisoning upon ethylene glycol electrooxidation on 3D PtBiAu, along with high CC bond cleavage and attainment of a ten‐electron complete electrooxidation via a CO‐free pathway. The interface‐rich 3D structure with "nanocontainer" function, electronic effect, and dual functional sites of "Pt–Au" or "Pt–Bi" enable the 3D PtBiAu to outperform industrial Pt black and 3D PtBi intermetallics significantly. The mass activity on the 3D Pt53.1 Bi43.4 Au3.5 intermetallics boosts to 28.72 A mgPt −1, higher than that reported in a previous study. The 3D Pt53.1 Bi43.4 Au3.5 exhibits superior performance to industrial Pt/C in direct ethylene glycol fuel cells (DEGFCs). The peak power density of 3D Pt53.1 Bi43.4 Au3.5 is 145/92 mW cm −2 in O2 /air (80 °C). Importantly, the cell voltage shows a negligible decay in both O2 and air during the 20 h durability testing. This study results in the development of novel 3D PtBiAu intermetallics as high‐performance anode electrocatalysts for application in DEGFCs. Abstract : A novel 3D structure for Au‐doped PtBi intermetallics woven by sub‐7 nm building blocks is achieved. The 3D Pt53.1 Bi43.4 Au3.5 as a high‐performance anode electrocatalyst promotes excellent power density and long‐term durability for practical, direct ethylene glycol fuel cells in both O2 and air.